GENERALIZED STRUCTURE OF THE SIMULATION MODEL OF THE GROUP ACTIVITY OF ACS OPERATORS - S. V. Kruglikov; A. R. Bekish (Informatika, 2018)
A formalized model of the activity of the collective of operators of an automated control system is developed, developed on the basis of the application of Buloshenko's aggregative approach in the form of a four-level aggregative system that includes aggregates of functional blocks, tasks, operators, and the collective of operators. Depending on the nature of the tasks being solved, it is proposed to use models of three levels: group, individual activity and an activity model that takes ergonomic factors into account. Generalized structural diagrams of all levels are presented, as well as the basic requirements and principles of the functioning of the blocks included in the model of the corresponding levels.